FOXA1 enhances antitumor immunity via repressing interferon-induced PD-L1 expression in nasopharyngeal carcinoma - Ying Liu; Bo Xiang; Wei Xiong; Pan Chen; Zhaoyang Zeng; Junshang Ge; Guiyuan Li; Mei Yi (Journal for ImmunoTherapy of Cancer)
Background Nasopharyngeal carcinoma (NPC) is a distinct subtype of head and neck cancer which is prevalent in south of China and southeastern of Asia. Consistent activation of interferon (IFN) signaling, and impairment of T cell mediated antitumor immunity is frequent in NPC. Forkhead box A1 (FOXA1) is one of the earliest discovered pioneer factors, which can open up compact chromatin structures to facilitate the binding of other proteins to chromatin.Methods By using RNA sequencing, it was discovered that FOXA1 suppresses the activation of the interferon signaling pathway and the expression of the related interferon-responsive genes in NPC cells. The effect of FOXA1 on programmed death-ligand 1 (PD-L1) expression in C666-1 and HK1 cells under conditions with or without IFN-γ was detected through quantitative PCR (qPCR), western blot, and flow cytometry. After co-culturing T cells with IFN-γ-treated NPC cells in vitro, apoptosis of CD8+ T cells and the expression of cytotoxic cytokines were assessed by flow cytometry. The cytotoxic effects of T cells on tumor cells in nude mice were measured by tumorigenesis in nude mice and adoptive T cell therapy. The effects of IFN-γ on the expression and nuclear localization of STAT1, as well as the colocalization of FOXA1 with STAT1 were detected by immunofluorescence, qPCR, western blot, and co-immunoprecipitation experiments.Results In this study, we reported that loss of FOXA1, a pioneer factor downregulated in NPC, results in activation of IFN signaling in NPC cells. Repression of FOXA1 facilitates IFN-γ induced PD-L1 expression, whereas overexpression of FOXA1 exerts the opposite effect. Mechanistically, FOXA1 interacts with STAT1 and inhibits IRF1 expression and binding to PD-L1 promoter on IFN-γ treatment. Co-culture with FOXA1-silenced NPC cells promotes apoptosis of in vitro activated tumor-specific CD8+T cells and reduces the expression of cytotoxic effector molecules. Furthermore, overexpression of FOXA1 increases the therapeutic efficacy of PD-L1 antibody (atezolizumab) against NPC in nude mice receiving adoptive T-cell therapy.Conclusions We demonstrated that FOXA1 prevents tumor immune evasion by inhibiting IFN-γ induced PD-L1 expression in NPC cells. Our research findings provide new insights into the immunotherapeutic biomarkers and targets for NPC, which is important for the clinical application of programmed cell death protein-1/PD-L1 antibodies in NPC.